Festival Beeldende Muziek 1987. (Hasselt : Provinciaal Museum, 1987)
Fähndrich, Walter ; Hess, Felix ; Kramer, Nina ; van Noorden, Leon ; Ollivero, Roberto ; Parlevliet, Nico ; Raes, Godfried-Willem ; Deboeck, Pierre ; Hirsch, Shelley
Festival Beeldende Muziek 1987, Provinciaal Museum, Hasselt, 1 mei - 6 juni 1987
boek